Penerapan Model Pembelajaran Kooperatif dengan Tipe Bertukar Pasangan untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA pada Mata Pelajaran Biologi - Tri Vanesa Anggraini; Ulyana Dinda Aritonang; Lisa Anggriani; Rully Ardiansyah; Febriani Tanjung (Education & Learning, 2022)
This type of research uses a cooperative learning strategy model of exchanging pairs using poster media and assignments in the form of LKPD in Biology subjects. The purpose of this study was to determine how much influence the effectiveness of the learning strategies used to improve learning outcomes and activities of class X MIPA 1 students at MAS Kuala Madu Langkat. It is known that the cooperative learning strategy model of exchanging pairs using poster media and assignments in the form of LKPD can be said to be effective because it can support the effectiveness and student learning outcomes.